Developing Mobile-Assisted Language Learning (MALL) Materials for ESL Learners - Sanjaya, Eko (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2024)
The development of technology has brought significant impacts on education. This creates much potential for the teaching and learning of English as a second language. With the great capability of the internet, educators can design powerful materials for efficient and effective learning. Mobile-assisted Language Learning (MALL) has become one of the popular research areas on technology in education in recent years for its advantages of flexibility of time and place. However, much only focus on a single application or platform implementation for the learning. This proposed study intends to integrate multiple internet-based platforms to support ESL learning. It aims to develop attractive and interactive learning materials that utilize Mobile-assisted Language Learning. This research uses the ADDIE method in developing the materials. To evaluate the materials, Technology Acceptance Model (TAM) will be adopted to investigate the participants